Power System Robust Day-ahead Scheduling with the Presence of Fast-Response Resources Both on Generation and Demand Sides under High Penetration of Wind Generation Units. (October 2021) - Mansoori, Alireza; Sheikhi Fini, Alireza; Parsa Moghaddam, Mohsen
Highlights: Robust operation planning with participation of fast-response resources both on generation and demand sides in order to providing required operational flexibility of power system; Implementing a decomposition-based approach to solve the proposed scheduling problem based-on column and constraint generation method; and. Considering the technical and economic limitations of each mentioned fast-response resources in order to providing the required power system flexibility. Abstract: Increasing penetration of renewable energy resources has led to the need for operational flexibility of the power system to cover the uncertainty and variability of these resources. Therefore, employing flexible resources during the operation time will play an important role in nodal power balancing, providing the required ramping capacity, and reducing the operating costs of the power system. Some of the most important flexibility resources in the power system are fast-response resources such as gas and combined cycle units with the ability to provide non-spinning ramping capacity, bulk energy storage systems with the ability to switch from charge to discharge mode and vice versa in short-time period, and demand response programs with fast-response to price and incentive signals, which prevent the occurrence of severe ramps by correction of the system load factor. Therefore, contrary to the existing literature, this paper examines the impact of the above-mentioned fast-response resources on the IEEE 6-bus and IEEE RTS24-bus test systems both on the generation side and the demand side in form of the proposed model for day-ahead scheduling problem under high penetration of wind-based units. Another important point is the need to co-optimize energy and required ramping capacity reserve of the system with efficient accuracy and tractability. Thus, in this paper, a mixed-integer, two-stage and tri-level robust model with adaptive approach has been utilized, which is solved by nested column-and-constraint generation decomposition-based algorithm in order to jointly clear the energy and ramping capacity reserve with the presence of fast-response resources. The results show that utilizing the potential of fast-response resources with the aim of providing operational flexibility reduces operating costs by up to 10.61%.